REALIZATION OF STRUCTURAL PROJECTS IS ONE OF THE WAYS OF DEVELOPMENT OF MACHINEBUILDING AND FOUNDRY PRODUCTION - V. I. Evseev; A. A. Ishchenko (Литьë и металлургия)
The main problems of foundry complex of our country, emerged for many years of functioning, are considered.